Drug‐Eluting Stent Targeting Sp‐1‐Attenuated Restenosis by Engaging YAP‐Mediated Vascular Smooth Muscle Cell Phenotypic Modulation - Chen Huang; Jie Zhao; Yuelin Zhu (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2020)
Background Activation of the YAP (Yes‐associated protein) pathway has been demonstrated to be related to smooth muscle cells (SMCs) phenotypic modulation and vessel restenosis. The aim of this study was to illustrate the molecular mechanisms that regulate the expression of YAP during the process of SMCs phenotypic switch. Whether the molecular basis identified in the study could be a potential therapeutic target for drug‐eluting stents is further tested. Methods and Results In cell culture and in rat carotid arterial injury models, Sp‐1 (specificity protein 1) expression was significantly induced, and correlated with SMCs proliferative phenotype. Overexpression of Sp‐1 promoted SMCs proliferation and migration. Conversely, siSp‐1 transfection or Sp‐1 inhibitor Mithramycin A treatment attenuates SMC proliferation and migration. Through gain‐ and loss‐function assays, we demonstrated that YAP was involved in Sp‐1‐mediated SMC phenotypic switch. Mechanistically, activated Sp‐1 regulated YAP transcriptional expression through binding to its promoter. Moreover, we fabricated a Sp‐1 inhibitor Mithramycin A‐eluting stent and further tested it. In the rabbit carotid model, Mithramycin A‐eluting stent inhibited YAP transcription and attenuated in‐stent restenosis through regulating YAP‐mediated SMC phenotypic switch. Conclusions Sp‐1 controls phenotypic modulation of SMC by regulating transcription factor YAP. Drug‐eluting stent targeting Sp‐1 might represent a novel therapeutic strategy to prevent in‐stent restenosis.